A Comprehensive Introduction to Artificial Intelligence Techniques for Advanced Wireless Networks: 5G and Beyond - Vaigandla, Karthik Kumar (IRO Journal on Sustainable Wireless Systems, 2025)
The fast development of wireless communication technologies, especially the move to the next generation of 6G wireless networks, has encouraged the demand for smart, flexible, and competent system design. Artificial Intelligence (AI) has become a game-changing enabler, providing robust solutions to handle the high level of complexity and dynamics in advanced wireless networks. This review paper introduces an in-depth overview of how AI methods can be used in the planning, optimization, and operation of 5G and beyond wireless networks. It offers a systematic inference about the incorporation of various AI approaches into major frameworks such as resource distribution, mobility management, network slicing, interference avoidance, and predictive maintenance. Moreover, the article discusses the difficulties associated with the application of AI-driven architectures in practice, pointing out concerns regarding data privacy, the interpretability of the models, computational load, and scalability. The review also presents emerging research directions and open challenges, aiming to provide researchers and practitioners with a foundational understanding of the integration of AI and next-generation wireless communication systems.
Keywords: Artificial Intelligence; Machine Learning; 5G Networks; Deep Learning; Network Optimization